2013
DOI: 10.1145/2427023.2427025
|View full text |Cite
|
Sign up to set email alerts
|

Accelerating Linear System Solutions Using Randomization Techniques

Abstract: We show in this paper how linear algebra calculations can be enhanced by statistical techniques in the case of a square linear system Ax = b. We study a random transformation of A that enables us to avoid pivoting and then to reduce the amount of communication. Numerical experiments show that this randomization can be performed at a very aordable computational price while providing us with a satisfying accuracy when compared to partial pivoting. This random transformation called Partial Random Buttery Transfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
65
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
2

Relationship

5
1

Authors

Journals

citations
Cited by 25 publications
(66 citation statements)
references
References 19 publications
1
65
0
Order By: Relevance
“…In this section we recall the main concepts and definitions related to RBT where the randomization of the matrix is based on a technique initially described in [10] and revisited in [2] for general dense systems. The procedure to solve Ax = b, where A is a general matrix, using a random transformation and the LU factorization is:…”
Section: Random Butterfly Transformationsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this section we recall the main concepts and definitions related to RBT where the randomization of the matrix is based on a technique initially described in [10] and revisited in [2] for general dense systems. The procedure to solve Ax = b, where A is a general matrix, using a random transformation and the LU factorization is:…”
Section: Random Butterfly Transformationsmentioning
confidence: 99%
“…Baboulin et al studied extensively the use of RBT for dense matrices and showed that in practice, d = 1 or 2 is enough; in most cases a few steps of iterative refinement can recover the digits that have been lost. They also showed that random butterfly matrices are cheap to store and to apply (O(nd) and O(dn 2 ) respectively) and they proposed implementations on hybrid multicore/GPU systems for the unsymmetric [2] case. For the symmetric case, they proposed a tiled algorithm for multicore architectures [3] and more recently a distributed solver [4] combined with a runtime system [5].…”
Section: Random Butterfly Transformationsmentioning
confidence: 99%
See 1 more Smart Citation
“…This technique was initially proposed in [16] in the context of general linear systems where the randomization is referred to as Random Butterfly Transformation (RBT). Then a modified approach has been described in [5] for the LU factorization of general dense matrices and we propose here to adapt this technique specifically to symmetric indefinite systems. It consists of a multiplicative preconditioning U T AU where the matrix U is chosen among a particular class of random matrices called recursive butterfly matrices.…”
Section: An Alternative To Pivoting In Symmetric Indefinite Systemsmentioning
confidence: 99%
“…These techniques were initially proposed in [16] and modified approaches were studied in [4,5] for the LU factorization. In this context, they are applied to the case of symmetric indefinite systems.…”
Section: Introductionmentioning
confidence: 99%